A cross-sectional analysis of the influence of corporate governance features on the organizational outcomes: An assessment - Yousif Alabdullah, Tariq Tawfeeq; Ahmed, Essia Ries (IIUC Studies, 2021)
This work aimed at testing the influence of corporate governance features on the organizational outcomes in one of the countries of the Gulf Cooperation Council (GCC) which is Qatar. The data was used for the organizations that belong to non-financial sector. The findings revealed that the size of audit commission, the board of directors size, and independency have positive influence on organizational outcomes represented by return on assets. In addition, the same positive influence could be found between the size of the audit commission and independency with return of equity as a second measurement of the organizational outcomes. Moreover, meeting of the board has a significant negative influence on organizational outcomes. The present work is considered as the first study that tests its predictor variables in its relationship with organizational outcomes. The considerable contribution of this study lies in identifying the previous studies gap for the GCC countries and analyses several viable studies that might probably be useful for improving corporate governance system in the non-financial sector. IIUC Studies Vol.17, December 2020: 9-26